Determinants of Stock Prices Infrastructure on the Indonesia Stock Exchange - Rizki Malik Fajar; Ardono Sepdantyo Yudo; Farah Margaretha Leon (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the relationship between a company's financial condition and the value of its shares in the market. The focus is on infrastructure sector companies in Indonesia listed on the stock exchange for the last three years (2021-2024). Similar studies use certain common financial variables, but this study tries a new approach by adding two additional variables, namely ROA (which reflects the efficiency of the company in generating profits from its assets) and company size (which describes the scale or size of the company). The aim is to see whether these two variables have a significant influence on the value of shares in the market. Using a quantitative approach and purposive sampling, the research gathered 172 observations from 43 companies. Panel data regression (cross-section and time-series) was applied through statistical software. This study found that several financial indicators such as EPS, NAVPS, and PER support that a significant and positive influence on stock prices. However, ROA in infrastructure companies in this study period, was not statistically proven to significantly affect stock prices. These findings highlight that not all financial indicators equally reflect market perceptions, particularly in capital-intensive and regulation-sensitive sectors like infrastructure. The study advises financial managers to enhance key indicators such as EPS, NAVPS, and PER to attract investors and boost firm value. For investors, the research offers guidance on which financial indicators to prioritize when evaluating stock prospects, while also cautioning that some metrics, like ROA, may not reliably predict price movements.